Pengelolaan Kelas Pada Pembelajaran Bahasa Jepang Di Kelas XI Bahasa SMA Karya Wisata Singaraja - Putu Ayu Sukasumartini; Desak Made Sri Mardani; Yeni Yeni (STKIP AGAMA HINDU SINGARAJA, 2023)
The purpose of this study is to describe classroom management activities carried out by teachers in Japanese language learning at Karya Wisata Singaraja High School. This study used descriptive qualitative data analysis techniques. Data collection was carried out using interview, observation, and documentation methods. The results of the study show that the classroom management carried out by the teacher in learning Japanese as a whole is fairly good. Classroom management is carried out to create and maintain optimal learning conditions, so that learning objectives can be achieved. The teacher has applied the principles of classroom management and the components of classroom management well. However, flexibility as well as finding and solving behaviors that cause problems are not carried out by the teacher. Teachers do not use laptops and LCDs because they are constrained by technological knowledge and limited school facilities.